A Pilot Empirical Study of “Intra-firm Boilerplate” CAM Reporting – DOW 30 Companies - SLAVIN, NATHAN S; Fang, Jianing (STIE Malangkucecwara, 2024)
On June 1, 2017, the Public Company Accounting Oversight Board (PCAOB) promulgated the new auditing standard AS 3101: The Auditor's Report on an Audit of Financial Statements When the Auditor Expresses an Unqualified Opinion. This new standard significantly expands the auditor’s report by requiring the inclusion of critical audit matters (CAMs) in an unqualified opinion. The primary objective of this paper is to examine whether the auditors were using an “intra-firm boilerplate” practice in CAM reporting. We analyzed the 10-Ks filed by the DOW 30 companies during the two-year fiscal periods of 2019 and 2020 by comparing the related CAMs. To run the binomial test on SPSS, we coded the relevant qualitative data in our data sheet before operationalizing them into the required binary format. Our empirical data indicate that most of the CAMs reported in fiscal year 2020 were either on new audit topics or with significant modifications in comparison to 2019. However, a substantial number (38%) of the CAMs reported in fiscal year 2020 were virtually the same as in fiscal year 2019. Our empirical results support former SEC chairperson Jay Clayton’s concern on “boilerplate” practice in CAM reporting.